1991
DOI: 10.1002/eji.1830211051
|View full text |Cite
|
Sign up to set email alerts
|

In vivo persistence of a HIV‐1‐encoded HLA‐B27‐restricted cytotoxic T lymphocyte epitope despite specific in vitro reactivity

Abstract: A large number of human immunodeficiency virus type 1 (HIV-1) specific HLA-restricted cytotoxic T cell (CTL) epitopes have been mapped, including an HLA-B27-restricted immunodominant epitope within p25gag. Accordingly, this segment of the HIV-1 provirus was amplified by the polymerase chain reaction from DNA derived from fresh uncultured peripheral blood mononuclear cells (PBMC) of four HLA-B27 HIV-1-infected individuals. In all cases the majority of infected PBMC bore sequences encoding the HLA-B27-restricted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 28 publications
(12 reference statements)
1
39
1
Order By: Relevance
“…The results from the present study contrast with the wellcharacterized role that escape mutations have been shown to play in progressive infection in HLA B * 2705 ϩ patients (23,25,29,38,(43)(44)(45). Similar to HLA B * 5701, B * 2705 is a Bw4 allele that has also been associated with slower progression of HIV disease.…”
Section: Discussioncontrasting
confidence: 99%
“…The results from the present study contrast with the wellcharacterized role that escape mutations have been shown to play in progressive infection in HLA B * 2705 ϩ patients (23,25,29,38,(43)(44)(45). Similar to HLA B * 5701, B * 2705 is a Bw4 allele that has also been associated with slower progression of HIV disease.…”
Section: Discussioncontrasting
confidence: 99%
“…There are limited prior reports examining escape from CTL responses in progressors, examining either a single case or one specific CTL epitope (28,35). Similar conclusions were recently reported in a cohort of chronically infected B57 ϩ subjects (36), limited to analysis of epitopes presented by HLA B57.…”
Section: Discussionsupporting
confidence: 55%
“…Some CTL epitopes persist within HIV-1 over years of infection despite the maintenance of CTLs that specifically recognize them (10,27,33,48,52,57). Thus, why escape mutations develop in some epitopes and not others remains unclear.…”
Section: Cd8mentioning
confidence: 99%